STRATEGI DINAS PERHUBUNGAN DALAM MENANGGULANGI KEMACETAN LALU LINTAS BERBASIS AREA TRAFFIC CONTROL SYSTEM DI KOTA BANDAR LAMPUNG - Asmaria Asmaria; Deni Santika (e-JKPP, 2019)
Congestion is a problem that often occurs in cities in Indonesia, Bandar Lampung City is one of the major cities in Indonesia that does not escape this problem. To overcome this bottleneck, the Bandar Lampung city government appointed the Department of Transportation to address the problem. One of the latest breakthroughs of the Bandar Lampung City Transportation Agency is to organize an Area Traffic Control System program.This study aims to look at the Strategy of the Department of Transportation in the Implementation of the APILL in the Area Traffic Control System in Bandar Lampung City in maintaining orderliness and smooth traffic in Bandar Lampung City. Strategy Implementation System according to Higgins which offers a Strategy system which is considered to be able to solve various problems in its implementation, namely: (1) Integral Planning and Control Systems, (2) Leadership, Motivation, and Communication Systems, (3) Human Resource Management, Organizational Culture . The method used is Qualitative Research, with Data Collection Techniques Through Interviews, Documentation, Observation.The results showed that the overall strategy of the Department of Transportation has been going well but there are still inhibiting aspects of the Department of Transportation's Strategy in Implementing Traffic Giving Tools Based on Area Traffic Control System in Bandar Lampung City. Not yet comprehensive socialization throughout the general public, especially road users, has caused many people not to know the Area Traffic Control System. in addition to the limited budget and the high cost of installing traffic control system areas, the development and addition of app traffic control system areas in the city of Lampung can not be fully implemented. the communication system that is established between the transportation office of the city of Lampung and the employees who handle the traffic control system is well established but the external communication with the parties involved has not been well established. the absence of a human resource development program that would hinder employees in terms of operating the components of the traffic control system area.